Drawing and painting portraits in watercolour - Thomas, D. A., 1938-2013 (Tunbridge Wells, Kent : Search Press, 2016)
Portraiture is one of the most rewarding painting disciplines. In this book, experienced portrait artist David Thomas shows that it need not be intimidating. Learn to use watercolour, pencil and charcoal to produce fresh and approachable portraits invested with life and character.
-- Introduction -- Materials -- Design -- Composition -- Proportion -- Pose -- Lighting -- Backgrounds -- Using line -- Sketching -- Drawing from life -- Drawing from photographs -- Drawing with pencil -- Using charcoal -- Drawing with charcoal -- Using watercolour -- Watercolour painting techniques -- Other useful techniques -- Colour and tone -- Painting from life -- Painting from photographs -- Perfecting your portraits -- Hair -- Eyes and hands -- Age -- The portraits -- Alexander -- Mother and baby -- Jilly -- Afterword -- Index
Includes index.
Keywords: Portrait painting -- Technique; Watercolor painting -- Technique; Portrait drawing -- Technique